Recent advances in research from plastic materials to microplastics - Priya Agarwal; Satya Prakash; Gaurav Saini; Ikhwan Syafiq Mohd Noor (Zaštita Materijala)
Plastics have become ubiquitous in our lives. Due to the ever-increasing population, rapid urbanization, and industrial advancement, the use of plastics has increased manifold. These plastic materials often disintegrate into microplastics (MPs) which are less than 5mm in size. MPs mostly enter aquatic habitats through improper waste management, illegal dumping, and unavoidable and unintentional discharges that take place during construction, manufacturing, farming, domestic consumption, and recreational activities. This review centers on exploring the origin, occurrence, and possible adverse effects of MPs on human well-being. Of the 485 literature reviewed for the study between 2014- 2023, 105 were found to be related to the MPs which were spread over 10 themes. The maximum number of papers were on sources of MPs, followed by MPs in freshwater ecosystems and waste management. The least number of literature was from the themes, transport of MPs and MPs in the soil environment. The literature was published mostly in China, India, Europe, and the Americas. Other countries like Australia, Latin America, Africa, and the Middle East contribute very little. The literature scan reveals that only 9% of all the generated plastic waste material is recycled, 12% is burned, and 79% of plastic litter is dumped in landfills and oceans. The dumped plastic settles and pollutes a variety of environmental matrices. MPs are intentionally manufactured to be added to personal care products that are washed down the drains through sewage or industrial wastewater. These MPs vary in density and colour, subject to the polymer type, and are present in varying sizes and concentrations in aquatic environments. The characterization of MPs originating from different types of polymer materials, in the reviewed literature, was performed based on the data obtained from Scanning Electron Microscopy Energy Dispersive Spectroscopy (SEM-EDS), Attenuated Total Reflection Fourier Transform Infra-Red spectroscopy (ATR-FTIR), Raman spectroscopy, and Atomic Force Microscopy (AFM). MPs have the potential to absorb harmful hydrophobic pollutants from the surroundings resulting in an indirect transfer of contaminants into the food web. Such MPs enter and affect humans, causing problems with the reproductive system, body weight, sex ratio, and live births. MPs pose a serious threat to organisms when ingested since they can obstruct the digestive tract, leading to oxidative and pathological stress, slowing down growth, and interfering with reproduction. Apart from the above, a comprehensive analysis of MP pollution, as well as its effect on human beings and the environment, has been discussed in terms of source identification and abundance. Also, has been discussed is a detailed review of the existing waste material recycled into new materials or reused without alteration or degradation to produce new energy sources. In the end, integrated strategies have been proposed to prevent the input of plastic waste material into the environment, by source control, improved plastic waste management, and techniques for degradation and conversion of MPs.